Sex- and dose-dependent abuse liability of repeated subanesthetic ketamine in rats - Schoepfer, Kristin J. (Physiol Behav, 2017)
RATIONALE: Subanesthetic ketamine (KET) elicits rapid, robust, but transient antidepressant effects. KET’s antidepressant actions can be augmented and maintained for a longer duration when repeatedly delivered. However, KET is recreationally abused, raising long-term treatment safety concerns. Women are more likely than men to seek treatment for depression, escalate from casual to compulsive drug use, and are more sensitive to antidepressants. Similarly, female rodents are more sensitive than males to KET’s rapid antidepressant-like behavioral effects; dose-response thresholds in these assays equal 2.5 and 5.0 mg/kg (i.p.), respectively. This suggests the utility of preclinical rodent models in optimizing sex-differential KET therapy protocols and minimizing adverse drug reactions. OBJECTIVES: Here, we assessed behavioral and biochemical correlates of abuse liability following six serial KET treatments on alternating days at three subanesthetic, antidepressant-like doses (2.5, 5.0, or 10 mg/kg, i.p.) in adult male and female rats. A potential role for ΔFosB-mediated transcription in the nucleus accumbens is outlined in the context of KET-mediated locomotor sensitization. RESULTS: Antidepressant-like threshold doses (2.5, 5.0 mg/kg KET) failed to evoke a conditioned place preference in all animals, but only males positively responded to a higher dose (10 mg/kg). Behavioral sensitization to 5.0 or 10 mg/kg KET’s locomotor-activating effects was established in both sexes, and females’ sensitized response to 5.0 mg/kg was greater than males’. KET-induced hyperlocomotion positively correlated with ΔFosB protein expression in the nucleus accumbens. rAAV-ΔJunD inhibition of ΔFosB-mediated transcription in the accumbens failed to block locomotor sensitization to 10 mg/kg KET. CONCLUSIONS: These data suggest that in rats, six alternating-day treatments with 2.5 mg/kg KET do not induce apparent behavioral signatures of abuse liability despite accumulation of ΔFosB protein in the accumbens. Additionally, females are more sensitive than males to KET’s locomotor-stimulant properties, both acutely and after repeated treatments. More studies are needed to determine brain regions and neural mechanisms responsible for KET-induced behavioral adaptations and to extrapolate these data to inform sex-dependent strategies for long-term KET therapy protocols for depression.